Targeting cancer prevention and screening interventions to LGBTQ communities: A scoping review. (14th December 2020) - Drysdale, Kerryn; Cama, Elena; Botfield, Jessica; Bear, Brandon; Cerio, Rebecca; Newman, Christy E.
Abstract: Although some people within LGBTQ communities are at risk of developing some cancers at higher rates than non‐LGBTQ people, there is limited evidence of the outcomes of targeted cancer prevention and screening interventions for these communities. This scoping review examined key findings regarding the feasibility, acceptability and efficacy of evaluated intervention studies conducted in high income settings and published in peer reviewed literature (2014–2020) by combining evidence of both cancer risk‐reducing behavioural interventions and screening and preventative practice interventions. While there is limited evidence of stronger outcomes from targeted interventions with cohorts of gender and sexuality diverse communities, compared with the use of mainstream or untailored interventions, there is stronger evidence that targeted interventions are more acceptable to these communities and may be more feasible in some contexts. Thus, there is benefit in understanding what targeting entails in these interventions, and to understand what influences acceptability, to inform the design and delivery of such interventions.